Implementasi Pembiayaan Mudharabah Untuk Kegiatan Usaha Masyarakat Sebagai Upaya Pemulihan Ekonomi Nasional Akibat Pandemi Covid-19 - Muhammad al Ikhwan Bintarto; Yudi Setiawan (ITB AAS INDONESIA Surakarta, 2021)
Covid-19 pandemic in 2020 so dangerious, not only dangerios for a healty but dangerious too the country’s economy. Much persons and companies in a country try how to recover country’s economy one of them Islamic banking and Islamic Micro Finance. This research is intended to find out how the implementation of mudharabah financing on society businesses in an effort to recover the economy due to the Covid-19 pandemic in Islamic Banking. This research use a qualitative method. The data for this research collected from book, aritcle and the result of this research is to know how islamic micro financing product can recover a society business can improve and recover after facing covid-19 pandemic.